The Relationship of Nurse's Compliance to Injection SOP and the Needlestick Accident in Irna 2 Surgery - Wiarto, Adi; Dafir Firdaus, Achmad; Harningtyas, Sismala (Green Publisher, 2022)
Needle stick injury is important problems in occupational safety in global health environment. In fact there are still occurrences of needle sticks that may be related to compliance. This study at to determine relationship between nurse adherence on injection procedure with needle sticks injury at IRNA 2 Bedah RSUD dr. Saiful Anwar Malang. Descriptive analytic cross sectional involving 39 respondents selected by purposive sampling technique. Data were collected with injection procedure observation sheet and needle injury observation sheet. Data analysis used correlation test with = 0.05. A total of 39 respondents, almost all of them 35 respondents or 89.7% had complied with Injection procedure and there was still one incident of needle stick injury in respondent. Statistical test results p value = 0.002 or p <0.05, there was a significant relationship between injection procedure and needle sticks injury at IRNA 2 Surgery RSUD Dr Saiful Anwar Malang